Attitude Towards Entrepreneurial Activities Among Yam Farmers In Ekiti State, Nigeria - Sola Emmanuel Komolafe (Serambi Journal of Agricultural Technology, 2021)
To understand the attitude of farmers towards yam entrepreneurial activities in Ekiti State, Nigeria, data were collected on respondents’ personal characteristics, attitude of farmers and factors influencing farmers’ attitude towards yam entrepreneurial activities. Data were analysed with frequency, percentage, mean and multiple regression analysis. Findings shows that respondents were married (81%), aware of agri-entrepreneurship skills (42%), experienced (30 years), inherited land (62%) and rarely visited major towns (41.2%). Majority (98.8%) of the respondents had positive attitude toward entrepreneurial activities. Marital status (p=0.023), years of experience (p=0.015) and land tenure (t= p=0.023) were determinants factors for positive attitude towards yam entrepreneurial activities among respondents. The study concluded that yam entrepreneur farmers in Ekiti State had positive attitude towards yam entrepreneurial activities. It was therefore recommend the need for intensive motivation programmes for yam farmers in Ekiti State by agricultural extension organisation with special focus on areas where respondents were found to have negative attitude.